Pengaruh Kecerdasan Emosional dan Motivasi Belajar terhadap Hasil Belajar Matematika Siswa SMP di Sekolah Maitreyawira Se-Sumatra - Henky Luwis; Isomudin; Muljadi (Sekolah Tinggi Agama Buddha Nalanda, 2023)
The objective of this research was to analyze the effect of emotional intelligence and learning motivation on Mathematics learning outcomes for junior high school students at Maitreyawira Schools in Sumatra. The research location was conducted at Maitreyawira Junior High School in Sumatra, located in Deli Serdang, Kisaran, Batam, and Palembang. The research population is all students of class VIII SMP in the academic year 2021/2022. The population was 530 students. Subject sampling used proportional random sampling with a sample of 228 students. This study uses a quantitative research approach with data analysis techniques using multiple linear regression. The results showed that there was a positive and significant effect of emotional intelligence and learning motivation on Mathematics learning outcomes, either partially or simultaneously. This is indicated by the significance value of the emotional intelligence variable of 0.000 and the significance value of the learning motivation variable of 0.000. While the value of the coefficient of determination (Adjusted R Square) is obtained at 0.544 and the regression equation of this study is Y = -47.546 + 0.359X1 + 0.494X2 + e